Comparative Analysis of Financial Statements With a Financial Ratio Approach: Study Case PT. Indofood Sukses Makmur Tbk. and PT. Siantar Top Tbk. Period 2022 - Angreyani, Andi Dewi (Economics and Business Journal (ECBIS), 2023)
The purpose of this study is to analyze the comparison of financial statements of two leading food companies in Indonesia, PT. Indofood Sukses Makmur, Tbk and PT. Siantar Top, Tbk. This research uses financial statements from PT. Indofood Sukses Makmur, Tbk and PT. Siantar Top, Tbk from 2022. The results of the data analysis show that PT. Indofood Sukses Makmur, Tbk and PT. Siantar Top, Tbk has an excellent liquidity ratio and the ability to settle debts. On the contrary, PT. Siantar Top has a better solvency ratio than PT. Indofood Sukses Makmur, Tbk. Activity ratio of PT. Indofood Sukses Makmur, Tbk and PT. Siantar Top, Tbk shows that both companies in terms of optimizing their assets, PT. Indofood is not good because the results are below industry standards. In addition, the profitability ratio of PT. Indofood showed better profit achievement performance than PT. Siantar Top, Tbk